Quadratic Spline and Heligman-Pollard Methods in The Preparation of Life Tables in Gegelang Village West Lombok - Fauzi, Andri Azmul; Anggraeni, Dara Puspita; Ridwan, Lalu Muhammad (KUBIK, 2023)
In this paper, we conduct research by compiling an abridged life table using the graduation method based on real data obtained at Gegelang Village, West Lombok. The graduation methods used in this study included quadratic spline and Heligman-Pollard. Based on the results, a special case of A was chosen as a method used to make a rough life table before graduation. After the graduation process, it was found that the Heligman-Pollard method was the most suitable. This is based on the chart produced using this method, which is monotonous in nature and does not fluctuate like other graduation methods. In addition, the life expectancy obtained at 65.72 years is close to West Lombok's life expectancy based on 2015.